Penilaian Pengetahuan, Sikap dan Perilaku Gizi Seimbang, serta Status Gizi pada Remaja di Daerah Rural: Penilaian Pengetahuan, Sikap dan Perilaku Gizi Seimbang serta Status Gizi pada Remaja di Sekolah Menengah Atas (SMA) Yayasan Bandung, Kabupaten Deli Serdang - Rukmana, Erni; Fransiari, Muhammad Edwin; Damanik, Kanaya Yori; Nurfazriah, Latifah Rahman (Universitas Airlangga, 2023)
Background: Malnutrition during adolescence can slow growth and delay puberty. Adequate nutritional knowledge, attitudes, and behavior among adolescents are crucial to prevent health issues that can continue into adulthood. Objectives: To assess the knowledge, attitudes, and behaviors related to balanced nutrition and nutritional status among adolescents at the Yayasan Bandung Senior High School, Deli Serdang Regency. Methods: The research design used was a cross-sectional design with a total of 80 adolescents aged 14 to 18 years at the Yayasan Bandung Senior High School, Deli Serdang Regency. The subject taking technique was stratified random sampling. Knowledge, attitudes, and behaviors of balanced nutrition were obtained through questionnaires. Height and weight data were analyzed using WHO Anthro Plus to determine the Z-score of Body Mass Index according to age. Data analysis used the Spearman test to determine the relationship between variables. Results: Most adolescents had good nutritional status, namely 68.8%, while the percentage of overnutrition and obesity was 18.8% and undernutrition was 12.5%. Adolescents have a high level of knowledge of balanced nutrition of 20 adolescents (25%). Balanced nutrition attitudes were categorized as high, namely 43 adolescents (53.8%), while high category balanced nutritional behaviors were only 6 adolescents (7.5%). The results of the bivariate test (Spearman Correlation) showed a relationship between attitudes and behavior-balanced nutrition (p<0.05). Conclusions: There is a relationship between attitudes and behavior of balanced nutrition in adolescence the Bandung Higher Education Foundation High School, Deli Serdang Regency.